2023
DOI: 10.1021/acs.langmuir.3c00592
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Leidenfrost Effect of a Cutting Droplet on a Microgrooved Tool Surface

Abstract: Regulation over the generation of the Leidenfrost phenomenon in liquids is vitally important in a cutting fluid/tool system, with benefits ranging from optimizing the heat transfer efficiency to improving the machining performance. However, realizing the influence mechanism of liquid boiling at various temperatures still faces enormous challenges. Herein, we report a kind of microgrooved tool surface by laser ablation, which could obviously increase both the static and dynamic Leidenfrost point of cutting flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…151 Such an increase in Leidenfrost point using microgrooved surfaces can improve the efficiency of machining processes. 152 Recently, Jiang et al 153 fabricated a multitextured substrate of solid micropillars with an insulating thick porous SiO 2 membrane in the midplane between the micropillar gaps and combined it with U-shaped bottom spacing between the micropillars. The prepared substrate increases the Leidenfrost temperature above 1150 °C for water on a steel substrate.…”
Section: ■ Interaction Of Liquid With Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…151 Such an increase in Leidenfrost point using microgrooved surfaces can improve the efficiency of machining processes. 152 Recently, Jiang et al 153 fabricated a multitextured substrate of solid micropillars with an insulating thick porous SiO 2 membrane in the midplane between the micropillar gaps and combined it with U-shaped bottom spacing between the micropillars. The prepared substrate increases the Leidenfrost temperature above 1150 °C for water on a steel substrate.…”
Section: ■ Interaction Of Liquid With Surfacesmentioning
confidence: 99%
“…An increase in the pitchthat is, the spacing between the micropillarsalso delays the Leidenfrost point by reducing the vapor pressure . Such an increase in Leidenfrost point using microgrooved surfaces can improve the efficiency of machining processes . Recently, Jiang et al fabricated a multitextured substrate of solid micropillars with an insulating thick porous SiO 2 membrane in the midplane between the micropillar gaps and combined it with U-shaped bottom spacing between the micropillars.…”
Section: Interaction Of Liquid With Surfacesmentioning
confidence: 99%
“…The vapor generated by evaporation forms a thin vapor layer that may prevent direct contact between the droplet and the particle, changing the particle–droplet contact from solid–liquid to solid–vapor–liquid and preventing the heat transfer between the solid and the droplet. This phenomenon is commonly known as the Leidenfrost effect. This has a very important impact on the safety and productivity of industrial processes such as fluid catalytic cracking (FCC), spray drying, spray cooling, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the residence time was independent of fluid types, and microtexture could increase the Leidenfrost temperature for water, but in reverse for ethanol. The single curve of the dimensionless maximum spreading factor versus the Weber number regarding water, ethanol, and FC-72 suggested the universality of the spreading dynamics in the film boiling regime regardless of liquid properties. Guo et al reported a kind of microgrooved surface tool by laser ablation, which could obviously increase both the static and dynamic Leidenfrost points of the cutting fluid by adjusting the surface roughness. Ma et al experimentally observed that the nucleate boiling with a violent atomization regime and the transition boiling regime were absent on superhydrophobic surfaces.…”
Section: Introductionmentioning
confidence: 99%